2020
DOI: 10.1007/s00520-020-05485-y
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of cardiorespiratory fitness in allogeneic stem cell transplant candidates prior to transplantation

Abstract: Purpose Cardiorespiratory fitness (CRF) seems to be prognostic prior to allogeneic stem cell transplantation (allo-HSCT). Influencing factors of CRF in allo-HSCT candidates have not been studied so far. Aim was to identify potentially influencing factors on CRF. Methods To assess CRF, a maximal cardiopulmonary exercise test (CPET) was performed on average 2.6 ± 7.2 days prior to admission. A regression analysis was conducted, with the following predictors: gender, age, body mass index (BMI), time between last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…(Limbach et al, 2021). In line with our findings, the VO 2peak values compared to a healthy reference group were significantly reduced in this study as well (Limbach et al, 2021). There is emerging evidence that very low cardiorespiratory fitness may predict mortality in haematological patients undergoing HSCT (Kelsey et al, 2014;Wood et al, 2013).…”
Section: Bio Impedancesupporting
confidence: 90%
See 1 more Smart Citation
“…(Limbach et al, 2021). In line with our findings, the VO 2peak values compared to a healthy reference group were significantly reduced in this study as well (Limbach et al, 2021). There is emerging evidence that very low cardiorespiratory fitness may predict mortality in haematological patients undergoing HSCT (Kelsey et al, 2014;Wood et al, 2013).…”
Section: Bio Impedancesupporting
confidence: 90%
“…Yet the large range in individual changes of cardiorespiratory fitness at 12-month followup, compared with baseline, might reflect the different time points where patients face complications, like infections or GVHD (Bishop, 2009;Mosher et al, 2009). (Limbach et al, 2021). In line with our findings, the VO 2peak values compared to a healthy reference group were significantly reduced in this study as well (Limbach et al, 2021).…”
Section: Bio Impedancesupporting
confidence: 85%
“…[ 37 ] Limbach et al found that older female patients with low physical activity and who received cardiotoxic therapy prior to allogeneic HSCT are at risk of decreased cardiorespiratory function. [ 38 ] Also, higher BMI and lower physical activity were significant predictors for low cardiorespiratory fitness. As seen in our case, the patient had a decline in distance by 44 m and required a RW.…”
Section: Rehabilitation Interventions For Functional Declinementioning
confidence: 99%
“…Patients had to perform until exhaustion starting at 20 W with a 10-W increase every minute. Exhaustion was determined by respiratory exchange ratio (RER) ≥ 1.1 or a heart rate ≥85% of the age predicted maximum [26,27]. The RER describes the ratio of carbon dioxide produced and oxygen consumed.…”
Section: Cardiopulmonary Exercise Testmentioning
confidence: 99%